ANALISIS TANGGUNG JAWAB PT. SUMBER ALFARIA TRIJAYA TBK TERHADAP PENGGUNAAN UANG KEMBALIAN KONSUMEN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN TERKAIT PUTUSAN MAHKAMAH AGUNG NOMOR: 533 K/PDT.SUS-KIP/2018 - Federico Octaviano B.; Ariawan Ariawan (Fakultas Hukum Universitas Tarumanagara, 2021)
Alfamart collects funds through the use of consumer change. The problem faced is the responsibility of PT. Sumber Alfaria Trijaya Tbk on the use of consumer change based on Law Number 8 of 1999 concerning Consumer Protection related to Supreme Court Decision Number: 533 K/Pdt.Sus-KIP/2018. The research method used in this paper is a normative juridical research method. The results showed that PT. Sumber Alfaria Trijaya Tbk to collect funds through the use of consumer change based on Law No. 8 of 1999 is based on the distribution mechanism of the results of public donations conducted by PT. Sumber Alfaria Trijaya Tbk, which throughout 2015 has collaborated with 8 credible foundations on a national and international scale. This can be proven by the Decree of the Minister of Social Affairs regarding the procedure for collecting donations, program period, donation collection area, beneficiary foundations, and also the obligation to disseminate information to the public in which the letter was officially issued by the Ministry of Social Affairs so that in its role as perpetrators of collecting donations who already have legal force. For the Alfamart or other business actors who raise social funds by quoting consumer change, it is expected to be able to carry out accountability to the public who have participated in donating by making financial reports that can be accounted for and easily accessible by the public